Report of a meeting between the Prime Minister, the Mining Association and Miners Federation, 23 April 1926 (page 39)
1926-04-23 "Report of a meeting between the Prime Minister, the Mining Association and Miners Federation, 23 April 1926 (page 39)" [g0492039.jpg], 23 April 1926, Trades Union Congress